Lithoprobe Phase IV: Multidisciplinary Studies of the Evolution of a Continent — A Progress Report - Clowes, Ron (Geoscience Canada, 1996)
Summary LiTHOPROBE is Canada's major national geoscience research project which combines multidisciplinary studies of the Canadian landmass and surrounding off-shore margins to determine how the northern North American continent has formed over geological time from 4000 million years ago to the present. The project has been instrumental in establishing a new era of collaboration among geologists, geochemists and geophysicists from universities, government and industry. It has brought new and exciting results to the attention of students, politicians, the media and the general public through its public outreach-communications program. But first and fore-most, Lithoprobe is a scientific project. This article highlights the accomplishments of the scientific programs from all transects (study areas) during the period 1993-1996 and the subsequent enhancement of our understanding of the tectonic development of our continent.